2020
DOI: 10.1016/j.ijpddr.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Dicyclanil resistance in the Australian sheep blowfly, Lucilia cuprina, substantially reduces flystrike protection by dicyclanil and cyromazine based products

Abstract: Late in 2017, field samples of the Australian sheep blowfly, Lucilia cuprina , were submitted by sheep producers from three states of Australia (South Australia, Victoria and New South Wales). Some were collected by submitters concerned about shortened periods of flystrike protection from dicyclanil based products. Neonate larval offspring from the NSW field samples survived and successfully completed their life cycles following exposure to dicyclanil and cyromazine at susceptible discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…While these flocks were not selected randomly and, hence, the results do not represent the real industry prevalence, the results suggest that resistance may be concerningly widespread. Sales 11 and Sales et al 12 also reported on an in vivo trial with strains composed of a mixture of resistant flies from various geographical locations. Significantly reduced protection periods for cyromazine and dicyclanil against resistant blowfly strains were demonstrated in this larval implant trial: strikes were observed (i.e., ‘protection failures’ occurred) at weeks 3, 4 and 9 for dicyclanil products with protection period claims of up to 11, 24 and 29 weeks, respectively.…”
Section: Insecticidesmentioning
confidence: 99%
“…While these flocks were not selected randomly and, hence, the results do not represent the real industry prevalence, the results suggest that resistance may be concerningly widespread. Sales 11 and Sales et al 12 also reported on an in vivo trial with strains composed of a mixture of resistant flies from various geographical locations. Significantly reduced protection periods for cyromazine and dicyclanil against resistant blowfly strains were demonstrated in this larval implant trial: strikes were observed (i.e., ‘protection failures’ occurred) at weeks 3, 4 and 9 for dicyclanil products with protection period claims of up to 11, 24 and 29 weeks, respectively.…”
Section: Insecticidesmentioning
confidence: 99%
“…However, there is a long history of development of blowfly resistance to various classes of insecticides (Levot 1995;Sandeman et al 2014;Heath and Levot 2015). The risk of widespread resistance developing to currently used insecticides (Sales et al 2020) emphasises the need for constant vigilance and for use of integrated pest management practices to prolong the utility of insecticides.…”
Section: Maintaining the Effectiveness Of Insecticides For Control Of Flystrikementioning
confidence: 99%
“…Appropriate application minimises the presence of a sublethal dose on sheep, which can increase the risk of resistance development and spread. The ability to maintain control and rotate insecticide use to minimise resistance development may become more constrained with the recent development of resistance to cyromazine and dicyclanil (Levot 2012(Levot , 2013Levot et al 2014;Sales et al 2020). Vaccines that indirectly or directly reduce the likelihood of flystrike may become an important adjunct in the integrated pest management strategy.…”
Section: Maintaining the Effectiveness Of Insecticides For Control Of Flystrikementioning
confidence: 99%
“…The sheep blowfly has shown an ability to develop resistance to some insecticides. 4,5 Resistance to the organophosphate class resulted in inadequate protection against flystrike when applied prophylactically, with their use continuing only as dressing treatments for existing strikes. Low-level resistance to the benzoyl phenyl urea compound, diflubenzuron, emerged in the field soon after its introduction for flystrike control in the early 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…By 2014, this low level of in vitro resistance to cyromazine was described as being 'quite common'. 8 Sales et al 5 recently described a number of strains of blowfly collected from regions within the state of New South Wales (NSW) that showed survivors when cultured on food sources containing a 'susceptible discriminating concentration' of dicyclanil. This study also reported on an in vivo larval implant trial using a blowfly strain showing high levels of in vitro resistance that showed significantly reduced flystrike protection periods following administration of dicyclaniland cyromazine-based products.…”
Section: Introductionmentioning
confidence: 99%